Fabrication of Hydroxyapatite Hollow Microspheres by the Composite‐Hydroxide Approach. Issue 9 (25th July 2014) - Hu, Luyang; Chen, Haibo; Zhang, Yumin; Li, Benxia; Zhang, Shanmei; Kleebe, H.‐J.
<x xml:space="preserve">Abstract</x> Hydroxyapatite (HAp) hollow microspheres with hierarchically porous structure and nanorice‐like architecture units were synthesized by the composite‐hydroxide approach. NH4H2PO4 was first reacted with hydroxides to form a hydroxide‐insoluble M3PO4 (the term M represents either Na or K). The diffusing M3PO4 at the liquid–solid interface then reacted with the Ca(OH)2, forming insoluble HAp hollow spheres by Kirkendall process. Results show that when reaction time is increased from 3 to 12 h, the average diameter of the microspheres increased from 2.64 to 4.16 μm. In addition, the size homogeneity of the hollow microspheres was improved gradually due to Ostwald ripening. The prepared hollow microspheres were treated by ultrasound, and nanorice‐like component units with a large mass of mesopores (<10 nm) were displayed. These prepared HAp hollow microspheres might be expected to apply to ion adsorption and drug delivery.